Leptin Administration Downregulates the Increased Expression Levels of Genes Related to Oxidative Stress and Inflammation in the Skeletal Muscle of ob/ob Mice - Neira Sáinz; Amaia Rodríguez; Victoria Catalán; Sara Becerril; Beatriz Ramírez; Javier Gómez-Ambrosi; Gema Frühbeck (Mediators of Inflammation)
Obese leptin-deficient ob/ob mice exhibit a low-grade chronic inflammation together with a low muscle mass. Our aim was to analyze the changes in muscle expression levels of genes related to oxidative stress and inflammatory responses in leptin deficiency and to identify the effect of in vivo leptin administration. Ob/ob mice were divided in three groups as follows: control ob/ob, leptin-treated ob/ob (1 mg/kg/d) and leptin pair-fed ob/ob mice. Gastrocnemius weight was lower in control ob/ob than in wild type mice (P<.01) exhibiting an increase after leptin treatment compared to control and pair-fed (P<.01) ob/ob animals. Thiobarbituric acid reactive substances, markers of oxidative stress, were higher in serum (P<.01) and gastrocnemius (P=.05) of control ob/ob than in wild type mice and were significantly decreased (P<.01) by leptin treatment. Leptin deficiency altered the expression of 1,546 genes, while leptin treatment modified the regulation of 1,127 genes with 86 of them being involved in oxidative stress, immune defense and inflammatory response. Leptin administration decreased the high expression of Crybb1, Hspb3, Hspb7, Mt4, Cat, Rbm9, Serpinc1 and Serpinb1a observed in control ob/ob mice, indicating that it improves inflammation and muscle loss.